PENGARUH PERSEPSI PEMBELAJARAN ONLINE TERHADAP KEMAMPUAN PESERA DIDIK MENYELESAIKAN SOAL ELASTISITAS DAN HUKUM HOOKE - Nurlela Nurlela; Tomo Djudin; Hamdani Hamdani (Universitas Tanjungpura, 2021)
AbstractThis study aims to determine the effect of online learning perceptions on the ability of students to solve problems of elasticity and Hooke's law at Madrasah Aliyah Yasti Sekura. This study used the Ex Post Facto method which involved 21 students of class XI science. The test in this study used a closed perception questionnaire totaling 20 items, and the questions were in the form of description questions with each question consisting of five questions representing each indicator. Based on data analysis, it was found that the average percentage of students' perceptions of the difficult category was 33.3%, the medium category was 42.9% and the easy category was 23.8%. And based on the results of data analysis, it was found that the average ability of students to solve problems was in the low category 19.0%, the medium category 66.7% and the high category 14.3%. In addition, there are differences in the ability to solve problems of elasticity and Hooke's law after online learning in terms of differences in perception (difficult, medium and easy) the results of the analysis are 0.048 <0.05. Students who have easy perceptions of the online learning process tend to be able to solve problems, so there is an effect of better learning outcomes than students who have difficult perceptions of online learning. Hooke's Law at Madrasah Aliyah Yasti Sekura.Keywords: Perception, Online Learning, Problem Solving Ability, Elasticity and Hooke's Law